Onomatopoeia in Aladdin Movie - I Ketut Mahendra Pradinatha; I Dewa Ayu Devi Maharani Santika (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
It is very common in daily communication to use words that imitate natural sounds, which are known as onomatopoeia. Onomatopoeia is also frequently used in movie dialogues, as these dialogues are designed to resemble everyday spoken language and assist characters in storytelling. This study aims to analyze the types and functions of onomatopoeia found in the Aladdin (2019) movie. The research method employed is a qualitative descriptive approach, using observation and note-taking techniques to collect the data. The classification of onomatopoeia types is based on the theory proposed by Akita and Dingemanse (2019), while the analysis of their functions refers to the framework by Roman Jakobson (1960). The results of this study reveal that onomatopoeia in Aladdin plays a significant role in expressing emotions, emphasizing actions, and enhancing the narrative atmosphere of the film. The use of onomatopoeia not only contributes to the authenticity of the dialogue but also strengthens the audience's emotional engagement with the characters and storyline. Therefore, onomatopoeia functions not merely as a sound effect, but also as a meaningful linguistic element in cinematic expression.